THE INFLUENCE OF SUSTAINABILITY REPORT TOWARDS THE COMPANY’S FINANCIAL PERFORMANCE: AN EMPIRICAL STUDY OF OIL AND GAS INDUSTRY LISTED IN INDONESIAN STOCK EXCHANGE (IDX) 2007-2011 - Husna, Prasida Nurul; Saraswati, Erwin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study is aimed to analyze the influence of Sustainability Report (SR) disclosure on the company’s financial performance (profitability, liquidity, book value, and leverage). Samples of this research are the oil and gas companies that published SR which listed in Indonesian Stock Exchange (IDX) during 2007-2011. Oil and gas companies were chosen because they were the largest contributor to the environment destruction. Data were collected by purposive sampling method and the samples used were 35 companies. This study uses linear regression for data analysis. The results show that the disclosure of SR have influence towards company’s financial performance especially profitability and liquidity. Whereas the disclosure of sustainability report do not have influence towards book value and leverage. This means that in the presence of SR disclosure by the company will increase the profitability and liquidity of the company, whereas for book value and leverage has no effect. The absence of significant influence of sustainability report towards book value and leverage appears due to the low levels of the disclosure of sustainability report in Indonesia. Keyword: Sustainability Report, profitability, liquidity, book value, leverage